Tradisi Sedekah Bumi Sebagai Pelestarian Budaya Lokal Di Desa Tebuwung Kecamatan Dukun Kabupaten Gresik: (Studi Living Qur’an) - Rosyidah, Ainur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This is research about sedekah bumi tradition in Tebuwung Village, Dukun District, Gresik Regency with the goal to describe the practice of sedekah bumi tradition in Tebuwung Village, then to describe the community's meaning of sedekah bumi tradition as local culture preservation in Tebuwung Village. This research uses descriptive qualitative field research methods and a living Qur'an approach using Karl Maanheim's analytical theory. Based on the findings of the meaning of sedekah bumi tradition to maintain local wisdom in Tebuwung Village, the objective meaning of this tradition is a tradition passed down from generation to generation which is carried out by the community as a form of gratitude to God by holding joint prayer events. The expressive meaning is to believe that the activity of giving alms to the earth can be blessed and protected by Allah, as well as building togetherness. The meaning of the documentary is that the tradition of giving alms to the earth, consciously or unconsciously, has become a routine that the Tebuwung community must carry out every year as a form of gratitude, sending prayers for deceased parents and clerics and preserving local culture to build the economy and harmony.